Dietetic intervention for inpatients on fluid‐only diets helps to achieve nutritional requirements. Issue 1 (14th June 2017) - Deacon, Sarah; Moran, Natalie; Laskey‐Gilboy, Bonnie; De Jonge, Maree; Rothery, Shonnel; Ahnon, Kristina; Whiting, Melissa; Emeto, Theophilus I.; Pain, Tilley
Abstract : Aim: The present study aimed to assess whether dietetic intervention helps patients on fluid‐only diets to meet their energy and protein requirements. This topic has not been previously investigated. Methods: A quasi‐experimental study of 57 patients receiving fluid‐only diets was conducted at The Townsville Hospital. The fluid consumption of participants was observed over 24 hours and was used to calculate total energy and protein intakes. The percentage of protein and energy requirements met was compared between patients receiving dietetic intervention and patients who were not. Results: Patients receiving dietetic interventions met a higher percentage of their energy requirements (75.88) than the control group (18.10) based on median intakes ( P < 0.001). Patients receiving dietetic intervention also met a higher percentage of their protein requirements (75.99) than the control group (13.80) based on median intakes ( P < 0.001). Stratification for age, body mass index (BMI) and fluid diet type showed no change in effect. Conclusions: This study shows that dietetic intervention enabled patients on fluid‐only diets to meet up to 80% more of their energy requirements and up to 95% more of their protein requirements. These results were consistent across age, BMI and fluid diet type. The significance of these differences has resulted in a change of clinical practice at the study hospital. All patients on fluid‐only diets for three days or longer are now blanket referred for dietetic intervention.